Defense and Counter-Terrorism in Israel - Michael Joshua Fleet (Politikon, 2015)
This paper is an analysis of the research question “is the Israeli defence policy of deterrence effective in minimizing domestic-terrorism?” Through a two-part examination of deterrence and then reconciliation, it explains that Israel has adopted an anachronistic geo-political view of the issues in West Bank/Gaza that must be updated to one of domestic counter-terrorism. The author argues that a reconciliation process would be a more effective method of countering domestic terrorism in Israel as it, if done correctly, can address the deeply-entrenched grievances felt by the groups involved with the conflict.